Signatures of a time-reversal symmetric Weyl semimetal with only four Weyl points. Issue 1 (December 2017) - Belopolski, Ilya; Yu, Peng; Sanchez, Daniel; Ishida, Yukiaki; Chang, Tay-Rong; Zhang, Songtian; Xu, Su-Yang; Zheng, Hao; Chang, Guoqing; Bian, Guang; Jeng, Horng-Tay; Kondo, Takeshi; et al.
Abstract Through intense research on Weyl semimetals during the past few years, we have come to appreciate that typical Weyl semimetals host many Weyl points. Nonetheless, the minimum nonzero number of Weyl points allowed in a time-reversal invariant Weyl semimetal is four. Realizing such a system is of fundamental interest and may simplify transport experiments. Recently, it was predicted that TaIrTe4 realizes a minimal Weyl semimetal. However, the Weyl points and Fermi arcs live entirely above the Fermi level, making them inaccessible to conventional angle-resolved photoemission spectroscopy (ARPES). Here, we use pump-probe ARPES to directly access the band structure above the Fermi level in TaIrTe4 . We observe signatures of Weyl points and topological Fermi arcs. Combined with ab initio calculation, our results show that TaIrTe4 is a Weyl semimetal with the minimum number of four Weyl points. Our work provides a simpler platform for accessing exotic transport phenomena arising in Weyl semimetals. Weyl semimetals are interesting because they are characterized by topological invariants, but specific examples discovered to date tend to have complicated band structures with many Weyl points. Here, the authors show that TaIrTe4 has only four Weyl points, the minimal number required by time-reversal symmetry.